Fertility Enhancing Surgeries that aid in natural Conception (Community Based Medical Journal, 2022)
Infertility is a rising problem worldwide, hampering the psychological and social wellbeing of thousands of couples. There is a huge financial involvement for its diagnosis and treatment as well. The main goal of reproductive pelvic surgery is to restore pelvic anatomy ensuring a patent and functional pathway for the sperm to reach the ovulated oocyte and a safe implantation into the endometrial cavity. The striking progress in assisted reproductive technology (ART) have upgraded the fertility outcome in despondent cases recently. This review article aims to highlight some surgical procedures commonly performed for better fertility outcome. It involves studying the available material in the textbooks, printed and online journals. The surgically treatable causes of infertility include Endometriosis, Polycystic Ovarian Syndrome, Tubo-peritoneal disease, Mullerian Anomalies and Uterine Myoma. In addition, Endometrial Polyps and Asherman’s Syndrome may also be treated surgically. A thorough evaluation and work up is mandatory to individualize the treatment plan for each patient. A wide spectrum of promising surgeries is available for the treatment of infertility. The surgical approaches have to be individualized depending upon the disease aspect. This is the sound way to measure the effectiveness of reproductive surgeries to restore the natural conception.CBMJ 2021 January: vol. 10 no. 01 P: 59-65